240 Epidemiology of illness in female athletes: a systematic review. (3rd March 2020) - Axon, Thomas; Perera, Nirmala
Abstract : Background: Illness prevention within elite sport can confer performance and health benefits to athletes. Despite the growing popularity and coverage of women's sport, little is currently known about the illness profiles of female athletes. Objective: To describe the incidence and nature of illness in female athletes. Design: This systematic review was prospectively registered (PROSPERO CRD42018092373). CINAL, Medline, PsychINFO, PubMed, SPORTDiscus were systematically searched from January 2008 to March 2018 inclusively. Peer-reviewed original research articles which reported the incidence and nature of illness in elite female athletes aged 18+ years were included. The risk of bias was assessed independently by two authors using the STROBE Statement Rating Criteria for systematic reviews. The included studies were mapped against the NHMRC evidence hierarchy. Main outcome measurements: Incidence and nature of acute and chronic illness. Results: 118 studies met the inclusion criteria; including 65 cohort studies (level ii/iii) and 46 cross-sectional studies (level iv evidence). The mean risk of bias was 16/22 (median=16, range 8–21). Of the included studies, 66 were in elite athletes (including 14 studies in Olympians), and 40 studies investigated collegiate/university athletes. Infections (primarily respiratory and gastrointestinal) were the most frequent cause of illness (46%), followed by mental health issues (20%), regardless of the sport or setting. Heterogeneity of illness definitions, severity classifications, and inconsistencies in exposure measures prevented any direct comparisons of illness incidence/severity across levels of competition. Conclusions: Illness prevention in women's sport is a novel and emerging research area. Currently there is a lack of consensus on illness data collection, and the majority of studies did not report important methodological information such as participant characteristics, or loss to follow-up. Owing to the lack of good-quality data, the findings are only able to provide a partial overview of the illness profile of female athletes, limiting the development of prevention interventions.